STRUCTURE OF THE PROJECT-ORIENTED ORGANIZATION ENERGY ENTROPY - S. Biloshchytska (Astana IT University, 2020)
This study presents the universal formalization of energy entropy for various organizations and its expression for project-oriented organizations. The energy entropy of organizations is determined by information entropy, total energy and the ratio of the achieved level of energy efficiency to the «ideal» level. Entropy is viewed as a measure of uncertainty in the information and organizational space. In the information space, it determines the measure of the missing information for making decisions. In the organizational space, entropy determines the level of entrepreneurial energy that is necessary for the successful operation of an organization in the implementation of projects and programs. The relationship between energy entropy and informational (structural) entropy of project-oriented organizations is established. It is determined that when adding a new project to the current totality, the organization must ensure a balance between the growth of uncertainty (information entropy) and energy efficiency. The method of «decomposition» of the total energy entropy of project-oriented organizations in the form of the sum of local energy entropies for projects is presented. The effect of adding a new project to the structure of a project-oriented organization on its integrated energy entropy is investigated. The presented results form a new look at the qualitative assessment of both a single project and the entire set of projects of a project-oriented organization.